ANALISIS PENGARUH FUNDAMENTAL PERUSAHAAN TERHADAP RISIKO SISTEMATIS SAHAM PADA PERUSAHAAN-PERUSAHAAN PROPERTI - Drs. Slamet Herutono (Akademi Akuntansi YKPN Yogyakarta, 2012)
This study investigate the impact of fundamental factors on the systematic risk (beta) stock. The data used in this research are the data of financial statement and stock price, obtain from Indonesian Capital Market Directory (ICMD) 2007-2009. The sample comprised 28 pooled companies from property industry listed on the Bursa Efek Indonsia (BEI) for the period of 2007 - 2009. The result found that current asset to total asset, debt to equity ratio, return on equity, earning pershare, and financial leverage simultaneously have significant effect on beta stock. But only current asset to total asset, return on equity, earning pershare, and financial leverage individually have significant effect on beta stock. Hence, the fundamental factor of company is not the only factor that influenced beta stock in the BEI.Keywords : fundamental factor, beta stock, panel data